Alterations in the pulmonary function tests of inflammatory bowel diseases - Fehmi ATEŞ; Melih KARINCAOĞLU; Süleyman Savaş HACIEVLİYAGİL; Mehmet YALNIZ; Yüksel SEÇKİN (Turkish Journal of Gastroenterology, 2019)
-